(untitled) (Progressive Agriculture, 2013)
This study was conducted to estimate the relative profitability of Maize production under different farm size groups. Data were collected from randomly selected 74 maize growing farmers of which 25 were small, 32 were medium and 17 were large considering the scope and potentials of maize production at Kishoregonj district. To achieve the objectives of the study, descriptive statistical techniques such as sum, average, standard deviation etc, were used. The major findings of the study showed that per hectare average total costs were Tk. 30,147.54, Tk. 31,892.00 and Tk. 34,059.00 for small, medium and large farmers, respectively. Per hectare gross return from maize production were Tk. 61,730.00, Tk. 79,716.00 and Tk. 75,707.00 for small, medium and large farmers, respectively. Per hectare gross margins from maize production was estimated at Tk. 36,836.00, Tk. 53,096.00 and Tk. 46,871.00 for small, medium and large farmers, respectively. Per hectare average net returns of maize were estimated at Tk. 31,583.00, Tk. 47,823.00 and Tk. 41,648.00 for small, medium and large farmers, respectively. The findings of the study revealed that medium farmers earned higher profit than those of small and large farmers. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16781 Progress. Agric. 21(1 & 2): 247 - 252, 2010